2018
DOI: 10.1093/milmed/usy064
|View full text |Cite
|
Sign up to set email alerts
|

Unexploded Ordnance Management

Abstract: The purpose of this Clinical Practice Guide is to provide details on the procedures to safely remove unexploded ordnance from combat patients, both loose and impaled, to minimize the risks to providers and the medical treatment facility while ensuring the best outcome for the patient. Military ordnance, to include bullets, grenades, flares, and explosive ordnance, retained by a patient can be a risk to all individuals and equipment along the continuum of care. This is especially true from the point of injury t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Mechanical non-powered manual saws and drills rather than saws and drills that use electricity and pneumatics must be used because of concerns about discharge and vibrations. 3,4 This letter emphasizes that there is a risk with impaled UXO injuries. Each reported case illustrates the importance of cataloguing experiences learned during crisis situation and bringing further insight to management of this very unusual and serious type of injury.…”
Section: Dear Editormentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanical non-powered manual saws and drills rather than saws and drills that use electricity and pneumatics must be used because of concerns about discharge and vibrations. 3,4 This letter emphasizes that there is a risk with impaled UXO injuries. Each reported case illustrates the importance of cataloguing experiences learned during crisis situation and bringing further insight to management of this very unusual and serious type of injury.…”
Section: Dear Editormentioning
confidence: 99%
“…2 There is little to be found in the literature regarding impaled unexploded ordnance (UXO) injuries. [3][4][5] In a review of 50 years of military experience and case reports from World War II, Vietnam, and Somalia, Lein et al found 36 patients with impaled UXO. Twelve out of 36 patients had injuries from impaled unexploded 48mm to 82 mm mortar ordnances.…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations